Risk for animal and human health related to the presence of dioxins and dioxin‐like PCBs in feed and food. (20th November 2018) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hogstrand, Christer; et al.
Abstract: The European Commission asked EFSA for a scientific opinion on the risks for animal and human health related to the presence of dioxins (PCDD/Fs) and DL‐PCBs in feed and food. The data from experimental animal and epidemiological studies were reviewed and it was decided to base the human risk assessment on effects observed in humans and to use animal data as supportive evidence. The critical effect was on semen quality, following pre‐ and postnatal exposure. The critical study showed a NOAEL of 7.0 pg WHO2005 ‐TEQ/g fat in blood sampled at age 9 years based on PCDD/F‐TEQs. No association was observed when including DL‐PCB‐TEQs. Using toxicokinetic modelling and taking into account the exposure from breastfeeding and a twofold higher intake during childhood, it was estimated that daily exposure in adolescents and adults should be below 0.25 pg TEQ/kg bw/day. The CONTAM Panel established a TWI of 2 pg TEQ/kg bw/week. With occurrence and consumption data from European countries, the mean and P95 intake of total TEQ by Adolescents, Adults, Elderly and Very Elderly varied between, respectively, 2.1 to 10.5, and 5.3 to 30.4 pg TEQ/kg bw/week, implying a considerable exceedance of the TWI. Toddlers and Other Children showed a higher exposure than older age groups, but this was accounted for when deriving the TWI. Exposure to PCDD/F‐TEQ only was on average 2.4‐ and 2.7‐fold lower for mean and P95 exposure than for total TEQ. PCDD/Fs and DL‐PCBs are transferred to milk and eggs, and accumulate in fatty tissues and liver. Transfer rates and bioconcentration factors were identified for various species. The CONTAM Panel was not able to identify reference values in most farm and companion animals with the exception of NOAELs for mink, chicken and some fish species. The estimated exposure from feed for these species does not imply a risk. Abstract : This publication is linked to the following EFSA Supporting Publications articles: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1136/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1137/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1374/full